2016
DOI: 10.18632/oncotarget.11236
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nomogram for identifying invasive pulmonary adenocarcinoma in patients with pure ground-glass nodule: A multi-institutional study

Abstract: PurposeTo construct a preoperative nomogram to differentiate invasive pulmonary adenocarcinomas (IPAs) from preinvasive lesions in patients with solitary pure ground-glass nodules (GGN).MethodsA primary cohort of patients with pathologically confirmed pulmonary solitary pure GGN after surgery were retrospectively studied at five institutions from January 2009 to September 2015. Half of the patients were randomly selected and assigned to a model-development cohort, and the remaining patients were assigned to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
(37 reference statements)
7
50
1
Order By: Relevance
“…Some researchers have begun to study the relation between smokers and lung cancer mortality [ 13 , 14 ]. She et al [ 13 ] identified preinvasive lesions and invasive pulmonary adenocarcinomas (IPAs) based on data from patients with solitary pulmonary pure GGNs that had been confirmed from January 2009 to September 2015. It was found that smoking status was one of the predictors of the invasive extent.…”
Section: Nodular Signsmentioning
confidence: 99%
“…Some researchers have begun to study the relation between smokers and lung cancer mortality [ 13 , 14 ]. She et al [ 13 ] identified preinvasive lesions and invasive pulmonary adenocarcinomas (IPAs) based on data from patients with solitary pulmonary pure GGNs that had been confirmed from January 2009 to September 2015. It was found that smoking status was one of the predictors of the invasive extent.…”
Section: Nodular Signsmentioning
confidence: 99%
“…These data indicated that many pGGNs were active and should not be neglected. Also, several studies demonstrated that 40.2-55.3% of pGGNs were invasive lesions [8][9][10][11]. The appearance of invasive components was considered to be a sign that tumor cells broke the balance of indolent period and entered the rapid growth time.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the data collected from five Chinese centers from patients with SPNs diagnosed by thinā€section CT (TSCT), which may better define the characteristics of nodules to develop a new model to estimate the pretest probability of malignancy. Nomogram has been accepted as a reliable tool to quantify the risk by incorporating important factors for clinical decisions . By creating an intuitive graph of a statistical predictive model, a nomogram gives rise to a numerical probability of a clinical event, such as malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Nomogram has been accepted as a reliable tool to quantify the risk by incorporating important factors for clinical decisions. [13][14][15][16][17] By creating an intuitive graph of a statistical predictive model, a nomogram gives rise to a numerical probability of a clinical event, such as malignancy.…”
Section: Introductionmentioning
confidence: 99%